1981
DOI: 10.1007/bf00554662
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of muzolimine and furosemide in patients with end-stage renal failure on chronic dialysis

Abstract: The pharmacodynamic effects of muzolimine and furosemide were compared in a single dose cross-over study in 8 patients on regular dialysis treatment, who had a residual diuresis of more than 300 ml/day. The study periods comprised two dialysis-free intervals of 3 days. On the second dialysis-free day either muzolimine 240 mg or furosemide 240 mg was administered orally. Urine was collected in 12-h periods on the pre-treatment, treatment and post-treatment days, and the excretion of sodium, potassium, urea and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
0
8
2
Order By: Relevance
“…Other actions of furosemide, such as anti-inflammatory effects, have already been reported. In our study, water and sodium ingestion was not restricted, in contrast to other study protocols [20,27]. However, through the food inquest, it was revealed that there was no difference in sodium ingestion between the DG and NDG (p = 0.443, Table 2).…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…Other actions of furosemide, such as anti-inflammatory effects, have already been reported. In our study, water and sodium ingestion was not restricted, in contrast to other study protocols [20,27]. However, through the food inquest, it was revealed that there was no difference in sodium ingestion between the DG and NDG (p = 0.443, Table 2).…”
Section: Discussioncontrasting
confidence: 39%
“…For example, Schimdt et al [20], upon comparing the diuretic effects of a single dose of 240 mg of furosemide to 240 mg of muzolimine found that both drugs clearly increased UV relative to the pre-treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in a more pronounced increase in diuresis and excretions of sodium and chloride than when 240 or 500 mg furosemide orally were used. These results were reached despite that half our patients had a mean diurnal control urine volume of less than 300 ml, while the patients in the two other studies had a diuresis of more than 300 ml/day [9,10]. In a recent study, it has been pre sumed that the remaining nephrons respond at least nor mally and may demonstrate an exaggerated response to amounts of diuretic reaching them [11], In a study in 8 patients with a creatinine clearance range of 5-18 ml/ min/1.73 m2, but not on chronic hemodialysis, Brater et al [11] demonstrated that a single intravenous dose of 160 mg furosemide is sufficient to reach the upper plateau 354 van Olden/van Meyel/Gerlag Effects of High-Dose Furosemide in Chronic Hemodialysis Patients of the dose response curve in each patient [II].…”
Section: Discussionmentioning
confidence: 71%
“…The increase in urinary vol ume and sodium excretion was limited in both studies, but there was a significant response of the remaining nephrons to these loop diuretics. We used a higher dose of oral furosemide than in earlier pharmacodynamic studies [9,10]. This resulted in a more pronounced increase in diuresis and excretions of sodium and chloride than when 240 or 500 mg furosemide orally were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation